A catalytic chiral gel microfluidic reactor assembled via dynamic covalent chemistry1. Issue 4 (16th April 2015) - Liu, Haoliang; Feng, Juan; Zhang, Jianyong; Miller, Philip W.; Chen, Liuping; Su, Cheng-Yong
<x xml:space="preserve">Abstract</x> A novel dynamic covalent gel strategy is reported to immobilize an asymmetric catalyst within the channels of a microfluidic flow reactor.